Results of Ranibizumab Treatment of the Myopic Choroidal Neovascular Membrane according to the Axial Length of the Eye. (13th May 2020) - Stepanov, Alexandr; Pencak, Martin; Nemcansky, Jan; Matuskova, Veronika; Stredova, Marketa; Beran, David; Studnicka, Jan
Abstract : Aim . A retrospective evaluation of the results of treatment of myopic choroidal neovascularization (mCNV) with intravitreal injections of ranibizumab in a pro re nata (PRN) regimen in three groups of patients distributed according to axial length. Methods . The paper presents a retrospective multicenter study carried out with the cooperation of several Departments of Ophthalmology in the Czech Republic. The study included 60 eyes of 60 patients suffering from mCNV, divided according to axial length into three groups. The first group consisted of 20 patients with an axial length of the eyes shorter than 28 mm (Group 1), the second group included 27 patients with axial lengths ranging from 28 mm to 29.81 mm (Group 2), and 13 patients had axial lengths longer than 30 mm (Group 3). All patients were first administered 3 initial intravitreal ranibizumab injections at monthly intervals (loading phase), and other injections were administered according to a PRN treatment regimen. Patients were evaluated before treatment and then at intervals of 3, 6, 9, and 12 months. The effect of ranibizumab treatment on the functional and morphological parameters of the affected eye was evaluated. Results . The average baseline BCVA ± SD in Group 1 was 52.6 ± 12.5 letters of ETDRS optotypes, and at the end of the one-year follow-up, it was 63.3 ± 11.8 letters. The average baseline of CRT ± SD in this group was 377.4 ± 80.0 μ m, and in the 12th month, it was 311.1 ± 63.7 μ m. The average baseline BCVA ± SD in Group 2 was 50.2 ± 9.0 ETDRS letters, and at the end of the follow-up, it was 60 ± 12.4 letters. The average baseline of CRT ± SD in Group 2 was 391.2 ± 85.2 μ m, and in the 12th month, it was 323.9 ± 91.2 μ m. In Group 3, the average baseline of BCVA was 48.5 ± 14.5 ETDRS letters, and at the end of the one-year follow-up, it was 55.7 ± 16.1 letters. The average baseline CRT ± SD for Group 3 was 342.1 ± 94.9 μ m, and after 12 months, it was 287.8 ± 88.4 μ m. An improvement of BCVA by ≥15 letters of ETDRS optotypes was achieved by 3 patients of 20 (15%) in Group 1, by 5 patients of 27 (18.5%) in Group 2, and by 3 patients of 13 (23.1%) in Group 3. All these changes were statistically significant in comparison with the input values p < 0.05 . Conclusion . Ranibizumab treatment in patients with mCNV in our study resulted in statistically significant improvement in BCVA and a decrease in CRT in all groups of patients. Our results from a routine clinical practice correspond with the results of large clinical studies; we confirm a particularly good effect of treatment in patients with axial lengths of the eye smaller than 28 mm.